Systems biology of metabolic and signaling networks : Energy, mass and information transfer - Saks, Valdur; Schlattner, Uwe; Aon, Miguel A. (Springer Series in Biophysics, 2014)
Systems Biology represents a new paradigm aiming at a whole-organism-level understanding of biological phenomena, emphasizing interconnections and functional interrelationships rather than component parts. The study of network properties, and how they control and regulate behavior from the cellular to organism level, constitutes a main focus of Systems Biology. This book addresses from a novel perspective a major unsolved biological problem: understanding how a cell works and what goes wrong in pathology. The task undertaken by the authors is in equal parts conceptual and methodological, integrative and analytical, experimental and theoretical, qualitative and quantitative, didactic and comprehensive. Essentially, they unravel the spatio-temporal unfolding of interacting mass-energy and information networks at the cellular and organ levels, as well as its modulation through activation or repression by signaling networks to produce a certain phenotype or (patho)physiological response. Starting with the historical roots, in thirteen chapters this work explores the Systems Biology of signaling networks, cellular structures and fluxes, organ and microorganism functions. In doing so, it establishes the basis of a 21st century approach to biological complexity.